Revisiting Early Sport Specialization: What's the Problem?. (January 2022) - Mosher, Alexandra; Till, Kevin; Fraser-Thomas, Jessica; Baker, Joseph
Context: The assumed risks of early specialization in sport are well known, with several international consensus statements advising against specialization in early athlete development. However, there have been recent calls for more focused research in this area. Evidence Acquisition: Research evidence from several scientific disciplines (eg, sport psychology, sports medicine, human development) were synthesized to develop a framework for practitioners working with adolescent athletes. Study Design: Narrative review. Level of Evidence: Level 4. Results: There appear to be risks associated with a highly specialized approach to athlete training, but the mechanisms driving these effects are largely unknown. Greater attention to understanding these mechanisms would help mitigate risk and develop stronger policy for athlete development. Recommendations for program modifications are provided. Conclusion: Early specialization remains an important topic for researchers and practitioners working with youth and adolescent athletes. However, more work needs to be done to provide truly evidence-based recommendations for youth athlete training.